Parenting Style and Attitude Toward English Learning of Public Middle School Students - Simanungkalit, Ate Gueen (LPPM Universitas Advent Indonesia, 2025)
This quantitative research investigates the influence of parenting styles on students’ attitudes toward learning English, including the descriptions of parenting styles and student attitudes toward learning English. The study involved 146 students from public middle schools in Airmadidi District, North Minahasa Regency, selected based on availability and willingness. Data was collected through a questionnaire and analyzed using descriptive and inferential statistics, including correlation and regression analysis. The results showed that parents employ various parenting styles – authoritative, authoritarian, and permissive - at moderate levels, with no extreme preference for any style. Despite this, students exhibited positive attitudes towards learning English, characterized by diligence and enthusiasm. The permissive parenting style did not significantly influence students’ attitudes. However, both authoritative and authoritarian styles individually had a significant impact. When the three parenting styles combined as predictors, permissive parenting remained insignificant, while authoritative and authoritarian styles significantly influenced students’ attitudes positively. This suggests that a mix of supportive authoritative and directive authoritarian parenting can positively affect students’ attitudes toward learning English.